Hypothesis and Theory: Collaborative Governance, Natural Resource Management, and the Trust Environment - Rapp, Claire (Frontiers in Communication, 2020)
Many natural resources are managed collaboratively by government agencies and affected stakeholders. Collaborative management is intended to reduce conflict, facilitate learning, and increase consensus among stakeholders. Previous work highlights the role of trust in developing a shared understanding and theory of change for participants in collaborations, but defines trust broadly. The presented work builds on a framework outlining four dimensions of trust important for collaborative natural resource management and argues there is a need to consider not only multiple forms of trust but multiple trust referents. In particular, it is proposed that the effect of individual trust on collaborative outcomes depends on the overall trust environment; when group trust is low individual trust has a limited effect on collaborative outcomes compared to when group trust is high. Measures to examine the multiple dimensions of trust and the trust environment are proposed. Practical implications for considering trust across dimensions and multiple trust referents are discussed.